2003
DOI: 10.1128/aem.69.12.7044-7057.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Community Structures and Sulfur Metabolism within Microbial Streamers in Japanese Hot Springs

Abstract: Community structures of submerged microbial slime streamers (SMSS) in sulfide-containing hot springs at 72 to 80°C at Nakabusa and Yumata, Japan, were investigated by molecular analysis based on the 16S rRNA gene. The SMSS were classified into two consortia; consortium I occurred at lower levels of sulfide in the hot springs (less than 0.1 mM), and consortium II dominated when the sulfide levels were higher (more than 0.1 mM). The dominant cell morphotypes in consortium I were filamentous and small rod-shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
73
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 56 publications
7
73
0
Order By: Relevance
“…Recently, two species of the genus Sulfurihydrogenibium were isolated and characterized as strict chemolithoautotrophs capable of using numerous electron donors and acceptors [H 2 , thiosulfate, elemental sulfur, sulfite, Fe(II), arsenite and selenite as electron donors and molecular oxygen, nitrate, Fe(III), arsenate and selenate as electron acceptors] Aguiar et al, 2004). Members of the genus Sulfurihydrogenibium play a significant role in sulfur-cycling (Skirnisdottir et al, 2000;Takai et al, 2002;Nakagawa & Fukui, 2003) and iron mineralization (Reysenbach et al, 1999) in terrestrial hot spring environments. Based on the phylogenetic analysis of 16S The GenBank/EMBL/DDBJ accession number for the partial 16S rRNA gene sequence of strain SS-5 T is AY686713.…”
mentioning
confidence: 99%
“…Recently, two species of the genus Sulfurihydrogenibium were isolated and characterized as strict chemolithoautotrophs capable of using numerous electron donors and acceptors [H 2 , thiosulfate, elemental sulfur, sulfite, Fe(II), arsenite and selenite as electron donors and molecular oxygen, nitrate, Fe(III), arsenate and selenate as electron acceptors] Aguiar et al, 2004). Members of the genus Sulfurihydrogenibium play a significant role in sulfur-cycling (Skirnisdottir et al, 2000;Takai et al, 2002;Nakagawa & Fukui, 2003) and iron mineralization (Reysenbach et al, 1999) in terrestrial hot spring environments. Based on the phylogenetic analysis of 16S The GenBank/EMBL/DDBJ accession number for the partial 16S rRNA gene sequence of strain SS-5 T is AY686713.…”
mentioning
confidence: 99%
“…The 16S rRNA gene sequence of strain TF1 T was identical or very closely related to partial sequences of the 16S rRNA genes that had been detected in the Nakabusa hot spring (Nakagawa & Fukui, 2003;Kubo et al, 2011;Everroad et al, 2012). In the maximum-likelihood phylogenetic tree, the novel isolate was shown to be a member of the family Thermodesulfobacteriaceae (Fig.…”
mentioning
confidence: 96%
“…Strain TF1 T was isolated from a neutral to slightly alkaline hot spring in central Japan, Nakabusa hot spring (368 239 N 1378 459 E), where the microbial community structure has been investigated by culture-independent methods (Nakagawa & Fukui, 2003;Kubo et al, 2011;Everroad et al, 2012). A sample of submerged microbial streamer was obtained from a pool of spring water (around 75 8C, pH 8.6-8.7).…”
mentioning
confidence: 99%
“…The type strain is AT1325 Over the past decades, microbiological investigations of a range of high-temperature marine and terrestrial environments have revealed the presence of a phylogenetically, metabolically and physiologically diverse community of thermophilic prokaryotes endemic to these particular habitats. Among the ubiquitous thermophilic taxa, members of the class Thermodesulfobacteria are commonly retrieved in hot biotopes, regardless of the geographical provenance of the samples (Skirnisdottir et al, 2000;Nakagawa & Fukui, 2003;Nakagawa et al, 2005).…”
Section: Strain At1325mentioning
confidence: 99%